Enhancement structural and signaling microenvironment of artificial tumor extracellular matrix for enhanced drug screening - Xingxing Liu; Yueying Ren; Sijia Fu; Yongjie Jiao; Xinan Chen; Fujun Wang; Lu Wang; Mengbo Hu; Chaojing Li (Journal of Tissue Engineering)
Bioscaffolds with characteristics of the tumor microenvironment is an important substrate to support the formation of multicellular tumor spheroids (MCTS). Conventional biomaterials promote MCTS formation using tumor extracellular matrix (ECM) components and exogenous growth factors, but lack individualized tumor cell niche construction which may restricts cell biology and drug discovery research. Herein, an ECM mimicked fiber composite dual-network hydrogel (FCDNG) was constructed. The 3D nanofibrous framework was introduced into the hydrogel by a “dispersion-swelling” method and an alginate/platelet-rich plasma (PRP) dual-network hydrogel was constructed by a simple “one-step” activation process. The scaffold can well control the physicochemical conditions that mimic the ECM structure and biomimetic mechanical properties. The fibrin formed by PRP can promote tumor cell proliferation, angiogenesis and cancer stem cell enrichment. Meanwhile, FCDNG has suitable degradation properties to meet the matrix remodeling requirements during the formation of MCTS. Tumor cells cultured in FCDNG had enhanced tumor stemness, proliferation, and resistance to chemotherapeutic agents, and thus providing an effective strategy for clinical drug evaluation.